Tensile behaviour of CFRP-glass adhesively bonded connections: double-lap joint tests and numerical modelling. (1st June 2022) - Rocha, Jorge; Sena-Cruz, José; Pereira, Eduardo
Highlights: Stiff and flexible adhesives yield to different CFRP-glass composite bond responses. Flexible adhesives smooth the stress concentration near the loaded end section. DIC method is extremely relevant in documenting the damage propagation mechanisms. Analytical and numerical tools accurately simulate bond responses. The local bond-slip laws are useful for modelling structural composite systems. Abstract: Within the context of glass structures, reinforcement strategies have been recently developed to prevent catastrophic failures by promoting the composite action between components. In this regard, the behaviour of adhesively bonded connections between glass and the reinforcement plays a crucial role. This paper presents an experimental, analytical and numerical study focussing on the bond behaviour of CFRP-to-glass adhesively bonded joints, comprising annealed glass sheets and CFRP laminates bonded with two stiff adhesives and one flexible adhesive. The experimental programme included (i) mechanical characterization tests and (i) tensile tests on CFRP-to-glass double-lap joints, evaluating the influence of the type of adhesive and the overlap length. Digital image correlation (DIC) method, analytical investigations and numerical modelling were performed to determine the local bond stress-slip laws for each adhesive, aiming at providing the required information to subsequently support the design of glass structural elements. Compared to the flexible adhesive, the stiff adhesives seem to promote more favourable interaction between the adherends; however, the former is better at promoting stress redistribution mechanisms, therefore, mobilizing longer bond lengths to transfer the tensile force between adherends. Adhesives with an extremely stiff response induce high stress concentrations in small areas and, consequently, the bonding system may fail prematurely at the glass adherend governed by localized phenomena, such as the low quality of glass processing methods, the high density of surfaces flaws and localized damage during handling.